Forage germplasm at the International Livestock Centre for Africa (ILCA): An essential resource for evaluation and selection - Hanson, Jean; Lazier, John R. (French Grassland Society, 1989)
Looks into ILCA's forage germplasm collection, characterization and initial evaluation and storage. Quantifies the genera, species and accessions of browse, grasses and legumes germplasm available in the ILCA genebank.